2019
DOI: 10.1111/1556-4029.14146
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Solvent‐based Method to Separate Duct Tape from Porous Surface for Fingerprint Development

Abstract: In this study, we have proposed a novel solvent‐based method using a specific concentration of 3M™ Novec™ HFE‐72DE and 7200 solvents to untangle duct tape from porous article with minimal impact to the quality of latent fingerprint deposited on the sticky‐side surface of duct tape. A series of experiments determined that a mixture of 30% HFE‐72DE:7200 (v/v) was found to be the most effective to separate various brands of duct tape from different types of porous surface, including office copy paper, newspaper, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Contacts of the section-tape with these oil-soluble reagents such as ethanol or xylol during staining, dehydrating, clearing, and mounting was supposed to contribute to weakened bonding forces between section and adhesive tape [ 46 ], which will lead to distorting the intact sections as seen in TSO in Figs 4 & 5 . Staining secondary to tape-aided sectioning as in TSO means that the tape—sections are contacted with oil-soluble solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Contacts of the section-tape with these oil-soluble reagents such as ethanol or xylol during staining, dehydrating, clearing, and mounting was supposed to contribute to weakened bonding forces between section and adhesive tape [ 46 ], which will lead to distorting the intact sections as seen in TSO in Figs 4 & 5 . Staining secondary to tape-aided sectioning as in TSO means that the tape—sections are contacted with oil-soluble solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Adhesive removal – A 30% HFE-72DE:HFE-7200 (v/v) solution is proposed to remove duct tapes from porous substrates, with minimal impact on fingermarks and higher performance compared to Un-Du [ 404 ].…”
Section: Fingermark Visualisationmentioning
confidence: 99%
“…Tape lifting has also been proposed as a forensic approach to recovering particulates and traces that offers the benefits of being cost-effective and creating a secure environment for the residues of interest [ [135] , [136] , [137] , [138] , [139] ]. Gwinnett et al reported using tape (Easylift) for lifting and monitoring micro polymers [ 140 ].…”
Section: Introductionmentioning
confidence: 99%